(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Objectives: To identify evidence based dietary patterns in preventing osteoporosis and fracture risk among both post menopause women and elderly men Design: Systematic review and meta-analysis. Participants: healthy postmenopausal women and elderly men with age range 39-80 years Measurements: PubMed, Google scholar databases were searched for relevant studies. Data extracted for all studies include study identification details, country of study conducted, subject baseline demographics, diet intervention details, duration of intervention details, dietary details of control and treatment groups, data details (included number of control and treatment subjects), exposure assessment method and outcome Results: Systematic review findings have found that vitamin D3 and calcium-fortified dairy product improves vitamin D status and reduces accelerated bone resorption. Dietary Intervention reporting C-terminal telopeptide (CTX) and P1NP (Procollagen Type 1N-Terminal Propeptide) outcomes were included in Meta analysis. Standardized mean differences, standard deviations, p values computed for 6 studies to undergo meta-analysis. Heterogeneity was significantly present for both CTX and P1NP, variance across the studies shown significance, positive association found between diet interventions and effect on bone biomarkers. Conclusion: A significant association found between fortified dairy and fortified orange juice with vitamin D and calcium in reducing risk of fracture among postmenopausal women and elderly men. A Med-Diet in combination with virgin olive oil or Nuts found to improvement in bone health among both adult and elderly men and women and a diet rich in vegetable, fruit, nuts, milk, high fibre bread, legumes found to low BMD levels and processed diet found to have low serum calcium levels causing bone resorption.